Assessment of heavy metals content and diversity of mercury-tolerant bacteria in heavy metal-polluted environmental samples and mercury bioremediation ability of isolated strains - Vinay Yadav; Anjali Manjhi; Nithya Vadakedath (Environmental Advances)
Mercury contamination disrupts ecosystems by causing toxicity and bioaccumulation in higher trophic levels. This study inspected the heavy metals content and the culturable diversity of mercury-resistant and detoxifying bacteria in samples from dumping site, thermal power plant and sewage treatment plant situated in/near Chandigarh, India. Most of the analyzed heavy metals were found above the permissible limit in these sites. Among 87 isolated bacteria, 45 could resist >200 µM ionic mercury (HgCl2). Markedly, 10 and 4 isolates harbored the key genes required for mercury detoxification, merA and merB gene, respectively. The merA gene-containing strain's phylogeny indicated the resistant strains belong to Alphaproteobacteria, Betaproteobacteria, Bacilli and Gammaproteobacteria. Nine isolates could volatilize HgCl2 efficiently, while two could volatilize organic mercury (CH3HgCl). The isolates Niallia circulans DCL_26, Serratia quinivorans DCS_A1, and Pseudomonas hibiscicola R_24 were found to resist and volatilize up to ≥300 μM HgCl2. Appreciably, S. quinivorans DCS_A1 could resist and remediate up to 6 μM of CH3HgCl. A 5-fold reduction in ionic mercury concentration was observed within 72 h of treatment for all three tested strains. Phytotoxicity assay performed using Arabidopsis thaliana and Brassica juncea seeds confirmed the strains DCL_26, DCS_A1, and R_24 have the ability to remove mercury from culture media as well as industrial effluent and reduce mercury toxicity significantly. The study provides a green technology based on microbial systems to remediate mercury-contaminated wastewater for its use in crop irrigation. However, further studies are required for the sustainable and safer application of these novel isolates to remediate mercury efficiently.